Evaluation of Two Models for Human Topoisomerase I Interaction with dsDNA and Camptothecin Derivatives - Laco, Gary S. (Public Library of Science, 2011)
Human topoisomerase I (Top1) relaxes supercoiled DNA during cell division. Camptothecin stabilizes Top1/dsDNA covalent complexes which ultimately results in cell death, and this makes Top1 an anti-cancer target. There are two current models for how camptothecin and derivatives bind to Top1/dsDNA covalent complexes (Staker, et al., 2002, Proc Natl Acad Sci USA 99: 15387–15392; and Laco, et al., 2004, Bioorg Med Chem 12: 5225–5235). The interaction energies between bound camptothecin, and derivatives, and Top1/dsDNA in the two models were calculated. The published structure-activity-relationships for camptothecin and derivatives correlated with the interaction energies for camptothecin and derivatives in the Laco et al. model, however, this was not the case for several camptothecin derivatives in the Stacker et al. model. By defining the binding orientation of camptothecin and derivatives in the Top1/dsDNA active-site these results allow for the rational design of potentially more efficacious camptothecin derivatives.